Cavernomas: analysis of 13 pediatrics cases - Saravia Toledo, Alejandro; Agras Menghi, Giuliana; Fernández, Adrián; Jaikin, Mario Sergio (Revista Argentina de Neurocirugía, 2025)
Background: cavernous malformations (CM) or cavernomas (C) are low-flow vascular malformations, angiographically occult and with magnetic resonance imaging characteristics that can define the time of haemoglobin degradation and even small fluid levels. They correspond to one of the main causes of cerebral bleeding in paediatrics and can be sporadic or familial and with multiple lesions. Microsurgical removal is recommended in symptomatic and anatomically accessible cases.Objectives: to report our case series of cavernomas and to compare it with the published literature.Methods: descriptive retrospective case series including patients diagnosed with CM between April 2016 and April 2022, via review of clinical records, neuroimages, operative and pathology reports. We focused on demographic data, clinical presentation, localization, treatment, outcome and neuroimaging findings.  Results: 13 children were included, 8 males and 5 females, with an age range from 7 months to 16 years (average age of 8.7 years). Three patients (23%) have a familial form with multiple lesions. Location was cortical supratentorial in 6 patients, deep supratentorial in 2, brainstem in 3, cerebellar in 1 and spinal in 1 child. Twelve cases (92%) presented with symptomatic haemorrhage. Eleven (85%) required surgery, all of them symptomatic: 9 (82%) due to a first haemorrhage and 2 (18%) due to rebleeding. Two patients remain in control due a deep location of the lesions. The 100% have a gross total resection, and 91% have postoperative neurological improvement. Mean time of follow-up was 2.5 years. Seven cases are remarked for further analysis.Conclusion: cavernomas are dynamic lesions that require surveillance; surgical opportunity must be considered, especially in paediatric population due to its long-life expectancy. Symptomatic and surgically accessible lesions were completely resected with favourable outcomes.
Keywords: Cavernoma; Cavernous malformation; Intracranial haemorrhage; Paediatric neurosurgery